Macronutrient Intake Patterns and Their Association with Adolescent Nutritional Status in Surakarta, Indonesia - Elsa Fara Islamiyah; Firmansyah Firmansyah; Dyah Intan Puspitasari (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Adolescence is a critical period for growth and development, during which adequate macronutrient intake plays a key role in achieving optimal nutritional status. In urban settings like Surakarta, Indonesia, dietary behaviors may vary due to socioeconomic diversity. Objective: This study aimed to examine the association between energy and protein intake and the nutritional status of adolescents in Surakarta. Methods: A cross-sectional study was conducted involving 94 adolescents aged 15–18 years. Macronutrient intake was assessed using 24-hour dietary recall, while nutritional status was measured using Body Mass Index-for-age Z-scores (BAZ). Data were analyzed using descriptive and inferential statistics with a significance level of p < 0.05. Results: The mean energy intake was 1376.07 ± 508.24 kcal and protein intake was 51.58 ± 22.63 grams. The mean BAZ score was –0.0395 ± 1.3157, indicating generally normal nutritional status. However, statistical analysis showed no significant relationship between either energy (p = 0.678) or protein intake (p = 0.642) and nutritional status. Conclusion: Although most adolescents had normal nutritional status, no significant association was found between energy or protein intake and BAZ. These findings highlight the need to explore other dietary and lifestyle factors influencing adolescent nutrition in urban Indonesian settings.